PENGABDIAN KEPADA MASYARAKAT MELALUI KULIAH KERJA NYATA (KKN) DI DESA PADANG PELASAN KECAMATAN AIR PERIUKAN - Salma, Salma; Oktavia, Acery; Rosika, Nanda; Dina, Dina; Julisen, Lekat; Bepa, Alga (CV. Kalimasada Group, 2024)
Community Service Lecture is a program that usually must be followed by students, especially those who are in their final year of college. There are many types of community service programs implemented by the UIN Fatmawati Sukarno Bengkulu campus, one of which is Mosque-Based Community Service. The purpose of this study is to present the results of the Community Service activities of group 126 in Padang Pelasan Village. Data collection techniques in this study were observation, interviews, and documentation. The results of this study present the main findings from the implementation of the community service program group 126 UIN Fatmawati Sukarno Bengkulu. The programs that we have implemented are community service programs by teaching reading the Qur'an, cleaning mosques, making mosque nameplates, visiting schools and teaching in Elementary Schools and cleaning sports fields.